Culturally sustaining pedagogy: Examining strategies to support the literacy development of Black students. - Florance, Daryl Bryan (2025)
Black students across our nation possess academic abilities that must be nurtured and supported within schools. The unfortunate reality is that Black students consistently perform below academic grade level proficiency in reading. This problem is consistent across grade levels, schools, and districts throughout the nation based on nationwide data. According to the National Assessment of Education Progress (2022), only 17% of Black students in fourth grade were at or above proficiency on the NAEP reading assessments, compared to 42% of White students who demonstrated proficiency. These gaps expand when adding the impact of poverty. Thirteen percent of Black students living in poverty were proficient, while White students not living in poverty were 49% proficient. These gaps have existed in our nation, state, and local districts for decades with minimal change (Au, 2016; Cohen, 2006; Coleman-King et al., 2023; Green & Giffore, 1980; Ladson-Billings, 2006; National Assessment of Educational Progress, 2022). There are many factors that influence this problem, including a lack of culturally sustaining teaching, a lack of access to high quality instruction, the presence of deficit ideology, and inequitable school policies and procedures (Bartanen & Grissom, 2019; Coleman-King et al., 2023; Khalifa, 2016; Ladson-Billings, 1994; Madkins, 2011; Paris, 2012; Sun, 2018). The factor that I focus on in this disquisition is the lack of culturally sustaining teaching (Ladson-Billings, 1995; Ladson-Billings, 2006; Paris, 2012). Black students often struggle to understand and recall key information in text. This happens due to a lack of connection between the content being taught and students’ own experiences and culture (Khalifa et al., 2019; Israel & Duffy, 2009; Ladson-Billings, 1995; Ladson-Billings, 2006). My theory of improvement holds that if there is an intentional focus on including culturally sustaining instructional strategies there will be improvements in students’ literacy development. I explore this theory in the unique context of a public charter school that serves a large population of Black students, many of whom are living in poverty. The improvement initiative includes professional development for teachers regarding culturally sustaining pedagogy. They learned specific culturally sustaining teaching strategies that will impact students’ literacy development. The professional development built the capacity of teachers to make better connections between the content being taught and students’ experiences. Teachers are utilizing the strategies learned in classroom settings, after receiving feedback from the design team, and they provide ongoing reflection regarding the process of implementation.